2017
DOI: 10.1002/sce.21326
|View full text |Cite
|
Sign up to set email alerts
|

The pursuit of a “better” explanation as an organizing framework for science teaching and learning

Abstract: This article seeks to make the case for the pursuit of a "better" explanation being a productive organizing framework for science teaching and learning. Underlying this position is the idea that this framework allows promoting, in a unified manner, facility with the scientific practice of constructing explanations, appreciation of its epistemic underpinnings and understanding of its outcome (i.e., conceptual understanding). The effective enactment of this framework in the classroom needs to be guided by a theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…They adopted the causal and unification models of explanations to guide their analysis. Papadouris et al's (2018) work focused on the pursuit of a better explanation through the development of a framework for science teaching and learning. In addition, this line of research also included studies in which researchers proposed various ways to assess scientific explanations that were not necessarily based on philosophical or theoretical background.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They adopted the causal and unification models of explanations to guide their analysis. Papadouris et al's (2018) work focused on the pursuit of a better explanation through the development of a framework for science teaching and learning. In addition, this line of research also included studies in which researchers proposed various ways to assess scientific explanations that were not necessarily based on philosophical or theoretical background.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In an empirical study of secondary preservice teachers' explanations, Richmond et al (2016) found that many in their methods course, regardless of major, struggled to provide causal explanations, connecting specifically to CE . Similar to Papadouris et al's (2018) discussion of the need for CCCs in constructing causal explanations, Richmond et al (2016) suggested beginning with CCCs for providing needed scaffolding.…”
Section: Resultsmentioning
confidence: 96%
“…Two of the articles focused on the connections between all of the CCCs and constructing explanations. In a theoretical paper, Papadouris et al (2018) underscored how CCCs can play a role in developing scientific explanations. The authors discussed how the use of CCCs allows for the generalizability of an explanation, an important feature of this scientific practice.…”
Section: Resultsmentioning
confidence: 99%
“…Education still encounters numerous problems and challenges which need attention to be put on more especially on educational policies of teachers' career development. (Granger et al, 2019;Livingston, 2014;Papadouris et al, 2018;Pryor et al, 2012).The problems in teachers' career development have become equal problems that spread in Indonesia. This is shown on several developing issues such as the problem of teacher quality which is argued by Sulistyo, the former chairman of PGRI states that the development of competence and career fail to go according to plan.…”
Section: Introductionmentioning
confidence: 99%
“…The mentioned conditions require capacity escalation of career development for teachers who are expected to motivate other teachers to conduct career development and innovation to increase their performance (Granger et al, 2019;Livingston, 2014;Papadouris et al, 2018;Pryor et al, 2012). Self-development, scientific writing, and innovative works are included in three requirements set to practiced by teachers in accordance to sustainable career development program as stipulated on Regulation of the Minister of Administrative Reform RB PermenPan No 16 of 2009 which unfortunately has yet shown any positive signs which cause teachers in large numbers are struggling to develop their career.…”
Section: Introductionmentioning
confidence: 99%